Defining the structural requirements for ribose 5-phosphate-binding and intersubunit cross-talk of the malarial pyridoxal 5-phosphate synthase - Derrer, Bianca; Windeisen, Volker; Guédez Rodríguez, Gabriela Liuvanova; Seidler, Joerg; Gengenbacher, Martin; Lehmann, Wolf D.; Rippe, Karsten; Sinning, Irmgard; Tews, Ivo; Kappes, Barbara (FEBS letters, 2010)
Most organisms synthesise the B(6) vitamer pyridoxal 5-phosphate (PLP) via the glutamine amidotransferase PLP synthase, a large enzyme complex of 12 Pdx1 synthase subunits with up to 12 Pdx2 glutaminase subunits attached. Deletion analysis revealed that the C-terminus has four distinct functionalities: assembly of the Pdx1 monomers, binding of the pentose substrate (ribose 5-phosphate), formation of the reaction intermediate I(320), and finally PLP synthesis. Deletions of distinct C-terminal regions distinguish between these individual functions. PLP formation is the only function that is conferred to the enzyme by the C-terminus acting in trans, explaining the cooperative nature of the complex.